IMPLEMENTASI FUZZY MAMDANI PADA LAMPU LALU LINTAS SECARA ADAPTIF UNTUK MEMINIMALKAN WAKTU TUNGGU PENGGUNA JALAN - Prasetya, Renaldi Primaswara (Jurnal Mnemonic, 2020)
Arrangement of the traffic lights is an effort that used to be able to regulate the vehicle rate on the highway. In fact, the volume of vehicles is increasing, and congestion can not be inevitable. Traffic light settings based on the phase of time which is fixed / static, less able to function well in a break down the congestion, remembering every street corner has a density of vehicles change adaptively. Hence the need for optimization of the arrangement on the traffic lights at the intersection of the highway in order to minimize the waiting time of road users. In this paper discussed making the control system simulation to determine the duration of the traffic lights adaptively at the intersection of highways using fuzzy mamdani algorithm. Determination of the traffic lights is determined by the parameters of the number of car, motorcycles, and the width of the road. From the testing with different parameter conditions can be obtained red light traffic has changed adaptively adjusting the conditions that occurred on the road.